MANIPULATIVE MOTION LEARNING APPROACH TO BASIC TABLE TENNIS TECHNIQUE SKILLS OF PUBLIC ELEMENTARY SCHOOL 1 CIHERANG STUDENTS - Asep Hidayat Muttaqin; Ribut Wahidi (Indonesian Journal of Education Teaching and Learning (IJETL), 2023)
Manipulative motion is something that is used to apply active motion to elementary school students, even manipulative motion can involve students in the activeness of student movement. With the aim of this research is to apply manipulative motion to the basic techniques of table tennis regardingforehand andbackhand students of SDN 1 Ciherang. In this study the authors used the pre-experimental method. The population consisted of 15 students at SDN 1 Ciherang. The author uses a sample of 15 students. To apply manipulative motion to the application of table tennis basic techniques to students at SDN 1 Ciherang. Descriptive statistical analysispretest the experimental group consisted of 10 grade V students at SDN 1 CIHERANG, for the experiment, the minimum score = 8, the maximum score = 12, the average = 9.40 and the standard deviation = 1.50. Analysispretest the control group of 10 students obtained a minimum value = 8, a maximum value = 11, an average value = 9.30 with a standard deviation = 1.05. Analysisposttest experimental group and control group on 10 grade V students of SDN 1 CIHERANG, forposttest the experimental group obtained a minimum value = 10, a maximum value = 14, an average value = 11.70 with a standard deviation = 1.49.Posttest the control group obtained a minimum value = 9, a maximum value = 14, an average value = 11.30 with a standard deviation = 1.76.